The Treatment Effect of Plantago Major on Lung Cancer Based on the Computed Tomography and Pathological Findings: A Case Report Study - Saade Abdalkareem Jasim; Bashar Mudhaffar Abdullah; Patricio Yánez-Moretta; Wesam R. Kadhum; Yasser Fakri Mustafa; Enas R. Alwaily; Munther Abosoda; Ali Alsalamy; Sada Ghalib Al-Musawi; Alaa A. Omran (Frontiers in Biomedical Technologies, 2025)
Purpose: Plantago Major (PM) is widely used for the treatment of different diseases due to several active compounds. Previous studies demonstrated the treatment effect of this plant on lung cancer cell lines. Here, we introduced a patient having lung cancer proved by Computed Tomography (CT) and pathological findings. The treatment effect of PM was assessed and presented based on CT and laboratory examinations for this patient as a first human case study.